3D printed magnetostrictive polymer composites (MPCs) for wireless stress sensing - Alex Abraham Paul; Quang Hao Nguyen; Wen Shen (Materials & Design)
As the mechanical performance of 3D printed polymers advances, there arises an urgent demand for enhanced methodologies to ensure their structural integrity. In this work, magnetostrictive polymer composites (MPCs) are investigated utilizing an ultraviolet (UV) curable epoxy resin through direct ink writing (DIW) for internal stress detection. A strong correlation between stress and magnetic flux change was observed within the printed MPCs. Impact from the inclusion of fumed silica (FS) as a rheological filler in the matrix were identified and investigated. The tensile strengths of the MPCs were in the range of 31 MPa–34 MPa. The changes in magnetic flux density (ΔB) of the MPCs under quasistatic loading were within the interval of 0.5 to 5.4 Gauss. A similar sensing behavior was obtained for the MPCs during cyclic loading. A similar sensing behavior was obtained for the MPCs during cyclic loading. Furthermore, it was found that incorporating the MPCs into specific layers further increased the tensile strength to over 40 MPa while still showing a significant ΔB response. Additionally, localized deposition of magnetostrictive particles at known stress concentrations emerged as a promising strategy for future stress-sensing endeavors.